The Role of Self-Confidence and Self-Awareness in Enhancing Academic Value: An SEM Analysis - Siswanto, Siswanto; Saimroh, Saimroh; Muthmainna, Alifah; Nurhijriah, Nurhijriah (International Journal of Social Learning (IJSL), 2024)
Self-confidence and self-awareness are psychological factors that play an important role in academic success, but the simultaneous relationship between the two to academic grades is not fully understood. This study aims to analyze the influence of self-confidence and self-awareness on the academic grades of high school students in Magelang using the Structural Equation Modeling (SEM) method. The study involved 50 students who were selected purposively, with data collected through a questionnaire based on a 5-point Likert scale. The instrument's validity was tested using Confirmatory Factor Analysis (CFA), while reliability was measured through Cronbach's Alpha. The results showed that self-confidence significantly influenced 0.490 academic scores, while self-awareness contributed 0.262. Combining the two explains 45.2% of the variance in academic scores. The research model fit well (GFI 0.91; CFI 0.93; RMSEA 0.058). This research emphasizes developing confidence and self-awareness to significantly improve students' academic achievement.